2001
DOI: 10.1002/yea.751
|View full text |Cite
|
Sign up to set email alerts
|

Genome organization of the linear cytoplasmic element pPE1B from Pichia etchellsii

Abstract: The linear cytoplasmic element pPE1B from Pichia etchellsii CBS2011 (synonym Debaryomyces etchellsii) was totally sequenced. It consists of 12835 bp and has a remarkable high A+T content of 77.3%. The termini of pPE1B were found to consist of inversely orientated identical nucleotide repetitions 161 base pairs long, to which proteins are probably covalently linked at the 5k ends. Ten putative genes (open reading frames, ORFs) were identified, covering 96.5% of the total sequence. The predicted polypeptides cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Thus, at least two enzymatic activities necessary for the capping of transcripts evidently reside in the ORF3 gene product. Predicted ORF3 gene products of all autonomous linear cytoplasmically localized yeast genetic elements that have been sequenced so far (Klassen, 2001) resemble capping enzymes known from cytoplasmic viruses (Poxviridae and Iridoviridae) in a way that putative guanylyltransferase motifs reside in the centre and triphosphatase motifs are located in the leading third of the polypeptide (Shuman, 1995;Larsen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, at least two enzymatic activities necessary for the capping of transcripts evidently reside in the ORF3 gene product. Predicted ORF3 gene products of all autonomous linear cytoplasmically localized yeast genetic elements that have been sequenced so far (Klassen, 2001) resemble capping enzymes known from cytoplasmic viruses (Poxviridae and Iridoviridae) in a way that putative guanylyltransferase motifs reside in the centre and triphosphatase motifs are located in the leading third of the polypeptide (Shuman, 1995;Larsen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As disruption of ORF1 had no influence on replication and maintenance, it appeared to be dispensable (Schaffrath et al, 1992), a finding which was supported by elucidation of the structure of pPE1B from Pichia etchellsii, in which homologues of all pGKL2-based genes but ORF1 were found to exist (Klassen, 2001); ORF2 encodes the element specific DNA polymerase, including the terminal protein (Tommasino et al, 1988;Takeda et al, 1996); the predicted ORF3 polypeptide, which is under investigation here, was found to share similarities with capping enzymes (Larsen et al, 1998); ORF4 may encode a helicase (Tommasino et al, 1988;Stark et al, 1990); ORF5 presumably encodes a ss-DNA binding protein (Schaffrath, personal communication); the predicted ORF6 protein encodes the RNA-polymerase for transcribing pGKL-based genes (Wilson and Meacock, 1988); ORF7 may be a subunit of the latter ; although essential, a function is not known for ORFs 8 and 9 (unpublished data); ORF10 codes for a terminal recognition factor, probably involved in initiation of replication of both elements (McNeel and Tamanoi, 1991); ORF11, a long-unappreciated gene of unknown function, occupies a small gap between ORF3 and ORF4 (Larsen and Meinhardt, 2000). For detailed information on the killer system, we refer to a recent review (Meinhardt and Schaffrath, 2001).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Replication of both autonomous and non-autonomous elements is initiated by protein priming, involving a viral B-type DNA polymerase fused to the terminal protein that remains covalently bound to the 5 0 ends of the plasmids (Hishinuma et al 1984;Stark et al 1984;Sor and Fukuhara 1985;Tommasino et al 1988;Hishinuma and Hirai 1991;Klassen et al 2001;Klassen and Meinhardt 2003;Jeske and Meinhardt 2006). Cytoplasmic transcription of linear plasmid-encoded genes involves a rather unique plasmid-encoded RNA polymerase and a mRNA-capping enzyme which resembles the capping enzyme of the cytoplasmic vaccinia virus (Wilson and Meacock 1988;Larsen et al 1998;Tiggemann et al 2001;.…”
Section: B Linear Plasmid-encoded Toxinsmentioning
confidence: 99%
“…As killer activity is observable in a partially cured strain that lacks pPin1-2 (Hayman and Bolen 1991), and large linear plasmids in such systems routinely confer functions for maintenance of the elements, rather than toxin production (Schaffrath et al 1992;Klassen et al 2001), pPin1-3 was expected to encode the killer trait. In this study, we provide a characterization of the nonautonomous killer element pPin1-3 of P. inositovora and its encoded toxin.…”
Section: Introductionmentioning
confidence: 99%